The Quit Propensity of Married Men - Shaw, Kathryn L. (Journal of Labor Economics, 1987)
This paper hypothesizes that the quit propensity of married men rises with an increase in their wives' income. Assuming that individuals are risk averse and that quitting is risky, the wife's income increases the husband's expected value of quitting by reducing the variance of expected family income. Using the longitudinal data from the Michigan Panel Study of Income Dynamics (PSID), the wife's income is found to have a large effect on quits. The average husband's quit rate increases by about 45% when the wife's income rises from zero to two-thirds that of the husband's. The wife's income effect nearly offsets the negative effect that marriage typically has on male quit rates.